Meningkatkan Profesionalisme Guru Agama Hindu - Ni Nyoman Sri Widiasih (UHN IGB Sugriwa Denpasar, 2016)
This paper aims to provide a correct understanding of the importance of quality and professionalism of Hindu religious teachers in education. A teacher of religion, especially Hindu religious teachers is not just a job assigned to transfer knowledge but also served to instill the values of the teachings of Hinduism to the learners. Hindu religious teachers are professional positions, hence a teacher demanded to carry out their duties professionally. The professionalism of a teacher can be seen from how to run any of the duties is always productive, innovative, efficient and effective and independent To be a Hindu religious teacher who is able to carry out their duties in a professional manner, the necessary efforts both from its own consciousness and on the government's efforts. In an effort to become a Hindu religious teachers qualified and professional, then a Hindu religious teachers is not enough to just rely on what the government has programmed as with training, workshops, competition research, as well as awards in the form of allowance teacher certification, and seminars, but a Hindu religious teachers are required to understand the teachings of Hinduism as a whole and want to fill themselves with the knowledge and responsiveness to changing times and technological advances. Thus, the material being taught will always correspond with the times and the material can be innovative, efficient and effective in their delivery in the classroom. Finally the success of a teacher of religion in their profession will appear on the character and attitude of the learners who become responsible, religious and good behavior.